A promising case of preclinical-clinical translation: β-adrenoceptor blockade from the oxygen-induced retinopathy model to retinopathy of prematurity - Cammalleri, Maurizio; Filippi, Luca; Dal Monte, Massimo; Bagnoli, Paola (Frontiers in Physiology, 2024)
Although compartmentalization of the eye seems to promote its experimental manipulation, drug penetration to its posterior part is severely limited by hard barriers thus hindering drug development for eye diseases. In particular, angiogenesis-related retinal diseases share common mechanisms and are responsible for the majority of cases of blindness. Their prevalence is globally increasing mostly because of the increased incidence of systemic pathologies in the adult. Despite the number of preclinical findings demonstrating the efficacy of novel treatments, therapy of retinal neovascular diseases still remains confined to intravitreal anti-vascular endothelial growth factor (VEGF) treatments with some extension to anti-inflammatory therapy. In the mare magnum of preclinical findings aimed to develop novel avenues for future therapies, most compounds, despite their efficacy in experimental models, do not seem to meet the criteria for their therapeutic application. In particular, the groove between preclinical findings and their clinical application increases instead of decreasing and the attempt to bridging the gap between them creates intense frustration and a sense of defeat. In this complex scenario, we will discuss here the potential application of the beta-adrenoceptor (β-AR) blockade with propranolol to the treatment of retinopathy of prematurity (ROP) in light of the major role that overactivation of the sympathetic system plays in retinal vessel proliferation in response to hypoxia as mimicked by the oxygen-induced retinopathy (OIR) model. Preclinical findings in the OIR model have been reported and discussed together with reviewing clinical trials using propranolol in ROP either per os or as eye drops. In this complex scenario, we will discuss here the role that overactivation of the sympathetic system plays in retinal vessel proliferation in response to hypoxia using the oxygen-induced retinopathy (OIR) model. The potential application of the beta-adrenoceptor (β-AR) blockade with propranolol to the treatment of retinopathy of prematurity (ROP) will be also discussed in light of preclinical findings in the OIR model and clinical trials using propranolol in preterm infants either per os or as eye drops.